MEDIA DEVELOPMENT APPLICATIONS BASED LEARNING LECTORAINSPIRE IPSTHE SUBJECT IN PRIMARY - Dwilita Astuti (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2019)
This study examined about the development of application-based learning media lectora inspire on Class V social studies subjects at SDN 1 Bandarjoyo, Batanghari subdistrict, East Lampung. The purpose of this research is to describe (1) the initial description of the need for learning media based on theapplication Lectora Inspire in Social Studies subjects in Class V; (2) an overview of the results of the development of learning media based on theapplication Lectora Inspire in Social Studies subjects in Class V, and (3) the feasibility of learning media based on theapplications Lectora Inspire in Social Studies subjects in Class V at SDN 1 Bandarjoyo, Batanghari Subdistrict, East Lampung. This research approach is research and development(research and development),the development model borg and gall. The process of developing learning media based onapplications Lectora Inspire in social studies subjects goes through 8 stages, namely preliminary research and data collection, planning, product development, validity test (expert test), revision I, small group test, revision II, and final product. data collection using a questionnaire instrument. Analysis of the data used is quantitative descriptive data analysis. The level of appropriateness of learning media based onapplications Lectora Inspire in social studies subjects was based on expert judgment of 4.35, media experts at 3.8, learning practitioners (teachers) at 4.55 and students at 4.54 so as to obtain a mean score of 4, 31 with a very good category that shows the results that the learning media is feasible to be used in the learning process for Class V students of SDN 1 Bandarjoyo, Batanghari subdistrict, East Lampung. Keywords: Learning Media,Application Lectora Inspire.